Effect of Plasma Treatment on Growth and Yield of Okra [Abelmoschus esculentus (L.) under Field Conditions - Kumar, Ravinder; Thakur, Ashok K.; Vikram, Amit; Vaid, A.; Rane, R. (International Journal of Bio-resource and Stress Management, 2017)
This study investigated the effect of cold plasma treatment on growth and fruit yield characters of okra [Abelmoschus esculentus (L.) cultivar P-8]. The experiment comprising of seeds of two different ageviz., ‘A1’ (One year old seed) and ‘A2’ (Two year old seed) and seven plasma treatments of seeds viz., ‘P1’ (only vacuum, no plasma treatment), ‘P2’ (3 minute), ‘P3’ (6 minute), ‘P4’ (9 minute), ‘P5’ (12 minute), ‘P6’ (15 minute) and ‘P7’ (Control–Without treatment) during 2014. The seeds with different combination of treatments were evaluated for different growth and yield parameters. It has been observed that the plasma treatment of 12 minutes duration on A1 seeds could significantly improve total emergence (27.72%), early days to 50% flowering and first fruit picking as compared to control. The plant height at final harvest (25.99%), harvest duration (25.38%), number of fruits plant-1 (40.29%), fruit weight (19.67%) and fruit yield plant-1 (8.16%) was significantly increased as compared to control. These results also indicated that cold plasma treatment might promote the growth and modify the speed of germination. It was also found that there is no significant effect of plasma take place on number of node to first flower, number of branches, fruit length and fruit diameter. Therefore, our results show that cold plasma treatment has important application prospects for increasing fruit yield of okra.